Attitude toward vital signs monitoring and its predictors among clinical nurses in Saudi Arabia - Alshehry, Abdualrahman Saeed (Frontiers in Public Health, 2024)
Positive attitudes toward assessing vital signs are essential in ensuring quality assessments and recognizing patients' declining conditions. However, few studies have been conducted that examine the attitudes of nurses toward this fundamental nursing skill. This research investigated the predictors of clinical nurses' attitudes toward vital signs monitoring in identifying the patients' deteriorating state. A cross-sectional, correlational study was conducted in two hospitals in Saudi Arabia. A sample of 427 clinical nurses was surveyed from February 2023 and April 2023 using a questionnaire on attitudes toward vital signs monitoring. The subscale "key indicators" achieved the highest mean, followed by "workload," "communication," and "knowledge." The hospital where the nurses work (Hospitals 1 and 2), younger age, gender (being male), marital status (being single), clinical area (working in intensive care unit), number of handled patients per shift (handling 11-20 and > 20 patients), and length longer years of experience were identified as significant predictors of the nurses' positive attitude toward vital signs monitoring. This research provides valuable knowledge on which aspect of the attitudes toward vital signs monitoring necessitates educational enhancement among clinical nurses. The factors influencing the clinical nurses' attitude toward vital signs monitoring reported in this study may be useful for nurse managers and other hospital policymakers in developing focused continuing educational interventions targeting enhanced vital signs monitoring competencies.